Changes in taxonomic structure and functional traits of nematodes as tools in the assessment of port impact. (5th October 2021) - Losi, Valentina; Grassi, Eleonora; Balsamo, Maria; Rocchi, Marco; Gaozza, Luigi; Semprucci, Federica
Abstract: Numerous anthropogenic activities take place within or nearby ports, thereby increasing environmental pressure in coastal zone that become the final destination of many environmental contaminants. Thus, port areas are crucial to understand the possible long-term effects of contaminants on metazoans that are at the base of the food webs. The port of Vado Ligure is the outlet to the sea of one of the largest industrial areas of the West Liguria (NW Mediterranean). Sediment quality was evaluated in twenty-eight stations at increasing distance from the port. The nematode fauna was characterised (i.e., assemblage composition, taxonomic diversity and functional traits) and organic matter quantity and composition and contaminant concentrations (heavy-metals, polycyclic aromatic hydrocarbons and heavy, long-chain hydrocarbons) were measured. The area resulted mainly polluted by mercury, followed by arsenic, zinc, and polycyclic aromatic hydrocarbons. The faunal distribution (both from a taxonomical and functional point of view) appeared influenced by the contamination, as well as by sediment granulometry and organic matter content and composition. According to nematode assemblages and environmental variables, two groups of stations showed the most marked differences: one located in front of the Vado Ligure port, characterised by the most contaminated stations, the highest organic matter content, and fine sediments, and the other one, close to Bergeggi Marine Protected Area, characterised by more pristine stations, low organic matter content and coarser sediments. A suite of nematode genera that may be considered as bioindicators of pollution and organic enrichment was selected. Maturity index (MI) resulted negatively affected by contamination, suggesting that the different proportion of the nematode life-strategies is useful in assessing the environmental quality of sediments. The ecological quality status of the sampled stations obtained using abiotic and biotic descriptors (i.e., contamination level, organic matter content and nematode diversity and maturity index) was compared. Both the abiotic and nematode variables showed a general consistency for the stations of the two groups characterised by the highest and the lowest levels of contamination and organic enrichment. Graphical abstract: Image 1 Highlights: Nematode assemblage was assessed in the seabed surrounding a port Nematode distribution was linked to contamination, granulometry and organic matter Maturity index (MI) resulted negatively affected by contamination A suite of nematode genera indicators of environmental quality was selected A multi-indicator approach resulted the most appropriate to assess port sediments